The future of the Environmentally sustainable national income - Hueting, Roefie (Ökologisches Wirtschaften - Fachzeitschrift, 2011)
Our planet is threatened by a wrong belief in a wrongly formulated growth. Estimating the distance between gross domestic product and environmentally sustainable national income can greatly improve the information about economic growth.